Incidental colorectal polyps in positron emission tomography - Yelsangikar, Amit (Medknow Publications & Media Pvt Ltd, 2012)
Fluorodeoxy glucose positron emission tomography/computed tomography (FDG PET/CT) is increasingly being used for diagnosing various malignancies and surveillance of cancer recurrence, staging and screening in high-risk individuals. Due to its high sensitivity in picking up small dysplastic lesions, incidental lesions are detected frequently. We present two patients who underwent PET CT as part of cancer screening and were incidentally detected with adenomatous colonic polyps. Colonoscopy and biopsy confirmed the diagnosis.